An analysis of regulation and governance for funeral social fund in Malaysia - Azrul Azlan Iskandar Mirza; Nurul Hanis Kamarudin; Khairil Faizal Khairi; Syadiyah Abdul Shukor; Nurul Aini Muhamed; Ahmad Fadly Nurullah Rasedee; Muhammad Suhaimi; Nuur Halimatus Saadiah Masrukhin; Aimi Fadzirul Kamarubahrin (Universitas Negeri Surabaya, 2022)
The funeral expense is becoming expensive. It will lead to funeral poverty whereby the next of kin of the deceased face difficulty paying funeral expenses. Increasing numbers of people seek financial management advice following bereavement, which can have a long-term effect on the grief experience and an individual's ability to manage. More should be done to encourage people on low incomes to prepare for death through simple advice and guidance. In Malaysia, a funeral social fund such as the Khairat death fund, in general, is financial assistance that is a grant to the family of the deceased for covering the cost and expenses of funeral processes. Khairat death fund was managed by community members or organizations in the areas. However, all this Khairat death organization moving with their own way as there is no legal jurisprudence as guidance to regulate and to be more systematic and synchronize management. Hence, this study will review regulation and governance for the funeral social fund in Malaysia.